2020
DOI: 10.1007/s10566-020-09559-0
|View full text |Cite|
|
Sign up to set email alerts
|

Strengthening the Power of Evidence-Based Prevention in Cooperative Extension: A Capacity-Building Framework for Translation Science-Driven Behavioral Health

Abstract: Background Translation science entails application of information gained through scientific research to practices intended to improve prevention and public health. The outreach arm of Land-Grant Universities—the Cooperative Extension System—is uniquely poised to facilitate this translation process and contribute to resolution of current substance misuse and other behavioral health issues. Objective This paper summarizes selected literatures th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Only 10% of survey respondents reported possessing adequate knowledge to address the opioid epidemic. Others have identified gaps in evidence-based practice and make a case for strengthening and expanding Extension capacity for behavioral health ( 21 ). These gaps in evidence-based practice are driven, in part, by limited capacity among Extension professionals at the community-level, an issue which must be remedied to accomplish the EOCRW recommendation to embed health promotion and prevention activities throughout Extension ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…Only 10% of survey respondents reported possessing adequate knowledge to address the opioid epidemic. Others have identified gaps in evidence-based practice and make a case for strengthening and expanding Extension capacity for behavioral health ( 21 ). These gaps in evidence-based practice are driven, in part, by limited capacity among Extension professionals at the community-level, an issue which must be remedied to accomplish the EOCRW recommendation to embed health promotion and prevention activities throughout Extension ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…Laying a strong foundation also involves integrating with existing national frameworks and recommendations including the Extension Opioid Crisis Response Workgroup (2018), National Framework for Health Equity and Well-Being (Burton et al, 2021), and Capacity-Building Framework for Behavioral Health Extension (Spoth et al, 2020). Such recommendations are addressed within each of the core functions.…”
Section: Laying the Foundationmentioning
confidence: 99%
“…Establishing such partnerships and linkages is a focus of prior recommendations. The National Framework for Health Equity and Well-Being (Burton et al, 2021) suggested developing partnerships across extension and academic-based health sciences and engagement in coalition work, while the behavioral health extension model (Spoth et al, 2021) proposed a communityuniversity partnership delivery system.…”
Section: Community Partnerships and Programmingmentioning
confidence: 99%
See 2 more Smart Citations